The origin of galactic metal-rich stellar halo components with highly eccentric orbits - Fattahi, Azadeh; Grand, Robert J. J.; Pakmor, Rüdiger; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2019)
Abstract. Using the astrometry from the ESA’s Gaia mission, previous works have shown that the Milky Way stellar halo is dominated by metal-rich stars on highl
Gesehen am 18.02.2019